Pengaruh Kepribadian, Kecerdasan Emosional dan Motivasi Terhadap Kinerja Driver Go Food Menurut Persepektif Bisnis Islam : (Studi Pada Driver Go Food di Bandar Lampung) - Fatih Fuadi; Adib Fachri; Niken Handayani (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2024)
Transportation makes it easier for people to carry out their daily activities. Transportation is really needed by the community, considering the density of people's activities which require moving from one place to another and also makes it easier for people to order the goods or food they want from a place that consumers want. Therefore, drivers with personality, emotional intelligence and good motivation are needed, where there is a decline in the performance of gofood drivers, one of which is the gofood driver in Bandar Lampung. This research aims to examine the influence of Personality, Emotional Intelligence, and Motivation on the Performance of Gofood Drivers in Bandar Lampung City from an Islamic Business Perspective. This research used a quantitative approach with a sample of 98 gofood drivers in Bandar Lampung. Sampling was carried out using an associative approach which connects one variable to another variable. The data analysis method uses SPSS (Statistical Program for Social Science) version 20 and then the data obtained is processed using SPSS 20 software. Data analysis in this research uses multiple linear regression analysis with Personality, Emotional Intelligence and Motivation as independent variables and performance as the dependent variable .Based on the research results, it shows that personality does not have a significant effect on the performance of Gofood drivers. Emotional Intelligence also has no significant effect on Gofood driver performance. Motivation has a positive and significant influence on Gofood driver performance. However, personality, emotional intelligence and motivation simultaneously have a significant effect on the performance of gofood drivers in Bandar Lampung City.